The contributions of the didactics discipline to teacher training - Matos, Emanuelle Oliveira da Fonseca (2021)
Didactics is fundamental for the exercise of teaching, however, many teachers do not know how to teach a Didactics subject effectively. Therefore, the following issue emerged: what is the contribution of the didactics discipline for students? Whose general objective is: to understand didactics and its role in the formation of future teachers. More specifically: identify a didactic as an instrument of práxis; establish a relationship between teacher training and didactics; and verify the contributions of didactics in the formation of future teachers. A survey conducted with four students from the Pedagogy course who have already taken the course of didactics at a higher education institution. The results showed that although the students relate didactics with teaching methods, they perceive the professors of this discipline as those who have a different approach from other professors with regard to the relationship between theory and practice.